PEML. Ecdotic Practice of Literary Modernity (Prassi Ecdotiche della Modernità Letteraria, 2017)
Two questions are connected to the choice to publish a new philological journal: the first concerns the scientific and cultural value of Philology; the second is the idea of Open Access journal.
Keywords: Open Access; philology